Perceptions of key informants on the provision of cervical cancer prevention and control programme in Uganda: implication for cervical cancer policy - James Henry Obol; Reema Harrison; Sophia Lin; Mark James Obwolo; Robyn Richmond (BMC, 2020)
Abstract Background Uganda has one of the highest burdens of cervical cancer globally. In 2010 the Ugandan Ministry of Health launched the Strategic Plan for Cervical Cancer Prevention and Control with the hope of developing cervical cancer policy in Uganda. This study explored the beliefs of senior key informants in Uganda about cervical cancer prevention, the control programme, and the relevance of cervical cancer policy. Methods We conducted 15 key informant interviews with participants from six organisations across Northern and Central Uganda. Participants were drawn from district local government health departments, St. Mary's Hospital Lacor, Uganda Nurses and Midwifery Council, non-governmental organisations (NGOs) and Ministry of Health in Kampala, Uganda. The interview recordings were transcribed and analysed using thematic analysis. Results Seven themes emerged relating to the cervical cancer prevention and control programmes in Uganda: (1) policy frameworks for cervical cancer, (2) operationalising cervical cancer prevention and control, (3) financial allocation and alignment, (4) human resources and capability, (5) essential supplies and vaccines, (6) administrative data and resource distribution, and (7) cervical cancer services. Conclusions The key informants perceive that the lack of a cervical cancer policy in Uganda is hindering cervical cancer prevention and control programmes. Therefore, the Ministry of Health and stakeholders need to work together in coming up with an effective policy framework that will accelerate efforts towards cervical cancer prevention and control in Uganda.